2003
DOI: 10.1002/mrc.1292
|View full text |Cite
|
Sign up to set email alerts
|

Structural elucidation and total assignment of the 1H and 13C NMR spectra of new chalcone dimers

Abstract: Conventional 1D NMR methods and 2D shift-correlated NMR experiments (COSY, HMQC, HMBC) were used for the structural elucidation and 1 H and 13 C chemical shifts assignments of four new types of chalcone dimers isolated from Myracrodruon urundeuva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
1
Order By: Relevance
“…These studies demonstrated that the cultivated species (shoots of height 40 cm) maintains its genetic characteristics regarding the pharmacological activity and produces qualitatively the same pharmacologically active constituents of the inner bark, the dimeric chalcones urundeuvines A, B, and C ( Fig. 1) (Bandeira et al, 2003) and tannins (Souza et al, 2007).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…These studies demonstrated that the cultivated species (shoots of height 40 cm) maintains its genetic characteristics regarding the pharmacological activity and produces qualitatively the same pharmacologically active constituents of the inner bark, the dimeric chalcones urundeuvines A, B, and C ( Fig. 1) (Bandeira et al, 2003) and tannins (Souza et al, 2007).…”
Section: Introductionmentioning
confidence: 76%
“…The dimeric chalcones urundeuvines A (26), B (31) and C (23) were observed at RT 6.12, 6.74 and 5.84 min in the UPLC-MS chromatogram of the inner bark extract, respectively. These substances were isolated earlier from the M. urundeuva inner bark by Bandeira et al (2003) and employed as analytical standards to confirm their presence. Furthermore, two novel urudeuvine A isomers were identified in the inner bark, with their peaks were observed at different RTs (6.29 and 6.62 min).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier chemical reports from the family showed phenolic compounds as major constituents: mangiferin from the root bark of Mangifera; quercetin, myricetin, and apigenin glycosides from the leaves of Rhus spp., robustafl avone from seeds of Rhus , bifl avones and bichalcones from Rhus (Chen and Lin, 1975;Masesane et al, 2000;Mdee et al, 2003), Myracrodruon (Bandeira et al, 2003) and Semecarpus (Rao et al, 1973;Murthy, 1992), fustin and fi setin from heartwood of Rhus spp. , and 2,3,6-trihydroxy benzoic acid and 2,3,6-trihydroxy (methyl) benzoate from Sorindeia (Kamkumo et al, 2012).…”
Section: Chemotaxonomical Importancementioning
confidence: 99%